Does aerobic exercise have a beneficial effect on plasma lipid profile in young soccer players? - Nowak, Robert; Kostrzewa-Nowak, Dorota; Eider, Jerzy (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Aerobic training plays an important role in soccer and is designed to improve players’ cardiovascular health. Aim of Study. The aim of this study was to assess the impact of a semi-long distance outdoor run on the lipid profile of soccer players. Material and Methods. Plasma activity of lipase (LP) and blood levels of triglycerides (TG), total cholesterol (TC), lipoproteins cholesterol: HDL-C and LDL-C, were determined among sixteen (8 male and8 female) soccer players, before, immediately after the run, and at the beginning of recovery time (30 minutes after the run). Results. The semi-long distance outdoor run caused a 30% decrease in the TG level in both studied groups (p = 0.0019 and p = 0.0002, pre-exercise vs. post-exercise for males and females, respectively). Post-exercise changes in TC(p = 0.0121 and p = 0.0158, pre-exercise vs. post-exercise for males and females, respectively) were observed. The changes in HDL-C level (p = 0.0001 pre-exercise vs. post-exercise) in males and LDL-C level (p = 0.00003 pre-exercise vs. post-exercise) in female soccer players were also found. Additionally, there were no post-exercise changes in LP activity among the studied female players, however, a significant (p = 0.0119) post-exercise decrease in LP activity among the male players was found. Conclusions. Post-exercise changes in lipid profile and LP activity (at least among males) are markers of soccer players’ biochemical adaptation to the training process.